Effect of the length and thickness of three constant temperature baffles on the natural convection heat transfer of nanofluid flow inside an enclosure affected by a magnetic field. (May 2023) - Wang, Dan; Hai, Tao
Abstract: This article examines the natural convection heat transfer (CNHT) in a two-dimensional square enclosure using the LBM. Nanofluid (NFD) is placed inside the enclosure and a magnetic field (MGF) is applied to the enclosure and NFD. The MGF has inclination angles ranging from 0 to 75° and its effect on the flow field and heat transfer (HTR) is evaluated. Also, the magnitude of the MGF varies by changing the Hartmann number (Ha) from 0 to 40. The left and right walls are hot and cold, respectively, and the top and bottom ones are insulated. Three baffles are placed on the hot wall, whose thickness is changed from 0.5 to 0.15 and their length is changed from 0.1 to 0.3. The results demonstrate that maximum HTR occurs on the upper part of the cold wall. The enhancement in the Ha reduces the value of Nu, and the increment of the inclination angle of the MGF enhances the value of Nu on the cold wall. An intensification in the thickness of the baffles (TOB) weakens the CNHT in the enclosure and thus reduces the amount of HTR. Also, enhancing the length of the baffles (LOB) weakens the vortex inside the enclosure.